Bioversity International Financial Statements 2021 for the year ended 31 December: Including independent auditor's report - Bioversity International (Bioversity International, 2022)
Bioversity International’s financial mandate includes maintaining accountability and transparency in its finances, and to evaluate and communicate direct impact from our work to our donors, partners and the wider research and development community.